THE PERCEPTIONS OF STUDENTS REGARDING THE WAYS OF COMMUNITY INVOLVEMENT IN PUBLIC SECONDARY SCHOOL AT DISTRICT KECH BALOCHISTAN - Bashir, Siraj; Shah, Nasreen Aslam; Karim, Hafsa; Farooq, Kinsa; Ahmed, Zohra Naseer (Humanities & Social Sciences Reviews, 2021)
Purpose of the study: The study was designed to investigate students' perception of community involvement in public secondary schools in the district KechBalochistan. Methodology: A quantitative method was employed for the current study and a descriptive study was designed to riposte the research questions. The sample size was delimited to 103 respondents. Data were gathered through Questionnaires which it was based on three clusters. Data were analyzed by utilizing the IBM SPSS version of 21. Main Findings: The researcher had found that the community involvement in school activities was not statistically significant. The majority of the student’s perception was that their parental community didn’t attend school activities, it was to a low extent. The perceptions of students about parental involvement in school debate activities plus school publications activities in addition to the parental involvement in school club activities were low. Applications of the study: The researcher had also suggested to the parents that their involvement in school activities plays a significant role in their academic performances. Novelty/Originality of the study: The outcomes of the research or study will motivate or encouraged the community members, especially the parent community to involve themselves more in the school affairs process to enhance the students learning achievement.